Analysis of the Implementation of Community Economic Empowerment Through the Concept of Religious Moderation - Mad Nasir; Hasan Mukmin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This article examines the implementation of community economic empowerment through the concept of religious moderation at State Islamic Higher Education Institutions (PTKIN), namely UIN Syarif Hidayatullah, UIN Sunan Gunung Djati, and UIN Raden Intan Lampung. Religious moderation at PTKIN is expected to serve as an instrument for strengthening community economics by integrating the values of tolerance, peace, and inclusivity into social and economic life. This study employs a qualitative method with a case study approach, involving lecturers, students, and surrounding communities as respondents. The findings reveal that the application of religious moderation at UIN Raden Intan Lampung contributes to strengthening social relations among communities, increasing community participation in sharia-based economic programs, and enhancing cooperation in socio-economic enterprises. Overall, religious moderation on campus has proven effective in promoting more inclusive and sustainable community economic development.